Application of Electric Current‐Assisted Sintering Techniques for the Processing of Advanced Materials. Issue 6 (13th April 2020) - Bram, Martin; Laptev, Alexander M.; Mishra, Tarini Prasad; Nur, Kushnuda; Kindelmann, Moritz; Ihrig, Martin; Pereira da Silva, Joao Gustavo; Steinert, Ralf; Buchkremer, Hans Peter; Litnovsky, Andrey; Klein, Felix; Gonzalez-Julian, Jesus; et al.
Abstract : Highly efficient energy conversion and storage technologies such as high‐temperature solid oxide fuel and electrolysis cells, all‐solid‐state batteries, gas separation membranes, and thermal barrier coatings for advanced turbine systems depend on advanced materials. In all cases, processing of ceramics and metals starting from powders plays a key role and is often a challenging task. Depending on their composition, such powder materials often require high sintering temperatures and show an inherent risk of abnormal grain growth, evaporation, chemical reaction, or decomposition, especially in the case of long dwelling times. Electric current‐assisted sintering (ECAS) techniques are promising to overcome these restrictions, but a lot of fundamental and practical challenges must be solved properly to take full advantage of these techniques. A broad and long‐term expertise in the field of ECAS techniques and comprehensive facilities including conventional field‐assisted sintering technology/spark plasma sintering (FAST/SPS), hybrid FAST/SPS (with additional heater), sinter forging, and flash sintering (FS) devices are available at the Institute of Energy and Climate Research: Materials Synthesis and Processing (IEK‐1). Herein, main advantages and challenges of these techniques are discussed and the concept to overcome current limitations is introduced on selected examples. Abstract : The Institute of Energy and Climate Research: Materials Synthesis and Processing (IEK‐1) has a broad expertise in the field of electric current‐assisted sintering (ECAS) techniques. It operates facilities including conventional field‐assisted sintering technology/spark plasma sintering (FAST/SPS), hybrid FAST/SPS (with additional heater), sinter forging, and flash sintering (FS), which are used for processing components for energy applications. Related examples are given.